Mathematical modeling of convective heat and mass transfer of a rotating nano-fluid bounded by stretching and stationary walls in a vertical conduit - Umadevi, Chatla; Dhange, Mallinath; Haritha, B. (Zielona Góra: Uniwersytet Zielonogórski)
The influence of thermal emission and unvarying magnetic field of convective heat and mass transfer of a rotating nano-liquid in an upright conduit constrained by a stretching and motionless wall is studied. The temperature, concentration profile, primary and secondary velocities have been computed through similarity transformation and fourth-order Runge-Kutta shooting technique.
Keywords: Brownian motion; magnetic field; stretching wall; vertical conduit; thermophoresis